Lighter Fluid Inhalation and Neurological Sequelae as a Forensic Case - Kaya, Ahsen; Temürkol, Selen Can; Özçalışkan, Burcu; Güler, Hülya (The Bulletin of Legal Medicine, 2020)
The use of inhalants, also known as volatile substances, is increasing all over the world. Lighter gas is one of the most frequently used inhalants, because it is easily accessible, can be bought legally and cheaply and has a pleasant effect in a short time.In this case report, an 18-year-old case that had a cardiac arrest in the street after lighter gas inhalation about three years ago was presented. He had a generalized tonic seizure during his follow-up in intensive care unit, and had changes secondary to hypoxic ischemic damage due to inhalation of butane gas in his cranial MRI and also had severe motor and mental neurological sequelae.In literature review, there were mostly autopsy studies of sudden death due to lighter gas inhalation. We think that presented case would contribute to the literature because it clearly reveals neurological sequelae as a result of lighter gas inhalation.
Keywords: lighter gas; volatile substance; inhalation; forensic medicine; ventricular fibrillation